(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A research work was undertaken to evaluate the feeding effect of concentrate supplementation on growth and reproductive performance of growing lamb upto first lambing. The trial was conducted at Char-elahi union, Chompanygonj, Noakhali. Thirty female sheep of about average 11.3 (±2.3) kg live weight and about 6-8 months of age were used and randomly allocated into three experimental diets, T0 (grazing), T1 (grazing + 1% concentrate supplement of live weight) and T2 (grazing + 2% concentrate supplement of live weight). The study revealed that the average daily DM intake was 261.00, 405.35 and 405.35g for diets T0, T1 and T2, respectively which was significantly (P≤0.01) different. DM intake when expressed as metabolic body weight also showed significant (P≤0.01) differences.DM intake as per cent of live weight were 1.96, 2.81 and 3.69 for diets T0, T1 and T2, respectively, which differ significantly (P≤0.05) among the treatment group. Daily grass DM intake was 261.00, 260.49 and 260.38g for diets T0, T1 and T2, respectively and this difference was not significant (P≥0.01) among the treatment group. Daily average live weight gain was 20.00, 35.50 and 44.00g for diets T0, T1 and T2, respectively. Live weight gain on diet T2 was significantly (P≤0.01) higher than that of diet T1 and T0. The results suggested that concentrate supplementation had higher growth response possibly due to better nutrient contents and their utilization. There were no significant (P≥0.01) effect on reproductive performances of service per conception, gestation length (d) and litter size (no.) of three dietary treatments. The Percentage of born alive T2 (100%) and T1 (90%) were higher in supplemented group compared to non supplemented T0 (70%) group. Birth weight of lambs of T2 (male-1.41kg, female, 1.06 kg) and T1 (male-1.21 kg, female-0.90 kg) group were significantly (P≤0.05) higher compared to that on only grazing group T0 (male-0.72 kg, female-0.56kg). The concentrate supplementation (2%) may be suggested for optimizing growth and reproductive performance of female sheep under grazing condition in coastal area. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 73-77